ANALISIS SUMBER DAYA PADA PROYEK KONSTRUKSI MENGGUNAKAN BAYESIAN NETWORK DAN STRUCTURAL EQUATION MODELING (SEM): STUDI KASUS PEMBANGUNAN GUDANG PT CKS - Purwanto; Joko Setiawan; Hermawan (ITB AAS Indonesia Surakarta, 2025)
The Success Of Construction Projects Heavily depends on the effective management of resources, including labor, materials, equipment, time, and cost. This study aims to analyze resource management in a warehouse construction project conducted by PT CKS and to identify key factors that influence project performance. A quantitative case study approach is employed, integrating Bayesian Network (BN) to model probabilistic relationships among physical resource variables, and Structural Equation Modeling (SEM) to analyze the causal relationships of psychological variables on project performance. Data were collected through questionnaires. The findings reveal that discrepancies in material procurement schedules, limited availability of skilled labor, and delayed decision-making are the main challenges. Meanwhile, motivation and organizational commitment have a significant impact on resource efficiency. The integration of BN and SEM provides a comprehensive perspective on the factors affecting project success and offers strategic recommendations for more optimal resource management. This research contributes both academically and practically to the field of construction project management.